Thermo-Optical Modulator Based on VO2 and Graphene Plasmonics - Sareh Vatani; Vahid Faramarzi; Jeongwon Park (IEEE Photonics Journal)
This paper details the design and theoretical analysis of a novel thermo-optical modulator that leverages the unique phase transition characteristics of vanadium dioxide (VO2) and the plasmonic properties of graphene. Employing a combination of transmission and reflection mode structures, the study explores four configurations designed to optimize modulation depth and minimize insertion loss. The analysis conducted using COMSOL Multiphysics with the finite element method (FEM) highlights the significant influence of geometrical parameters on the modulator’s performance. The specific attention to the interaction between VO2’s phase transition at critical temperatures and graphene’s conductivity adjustment provides insights into the dynamic control of optical signals in the mid-infrared spectrum.